Dual-targeting liposomal delivery of sorafenib and docetaxel for enhanced synergistic therapy in advanced hepatocellular carcinoma - Yawen Yao; Yue Hu; Xinwang Meng; Fenyan Feng; Feng Xu; Guangji Wang; Hua Yu; Juan Li (Elsevier, 2024)
Patients with advanced hepatocellular carcinoma (HCC) are not sensitive to sorafenib (SOR), therefore, combination therapy is required. In this study, an improved thin-film dispersion and post-insertion anchoring technique was utilized to construct a dual-targeted co-delivery SOR and docetaxel (DTX) liposome drug delivery system, folate/chondroitin sulfate with SOR/DTX-modified liposomes (FA/CS@SDLP), to jointly enhance the anti-recurrence and metastasis of HCC. FA/CS@SDLP can establish the gradual release of the two drugs because of successful lysosomal escape in the condensed hyaluronidase environment. The results indicated that modification with folate (FA) and chondroitin sulfate (CS) significantly enhanced the cellular uptake of FA/CS@SDLP and the internalization of SOR/DTX in HepG2 cells through FA and CD44 receptor-mediated endocytosis. Compared to free drugs or the mono-targeted liposomal system (FA@SDLP), FA/CS@SDLP presented higher potency against HepG2 cells regarding pro-apoptosis, anti-proliferation, and anti-metastasis (migration and invasion). Moreover, a more satisfactory antitumor efficacy was observed for FA/CS@SDLP in the pulmonary metastasis of HCC in a mouse model. In summary, dual-targeted co-delivery of liposomes can synergistically treat HCC recurrence and metastasis, providing a new approach for the clinically accurate treatment of HCC.